Investigation on interface stripping damage at high-temperature using microstructural analysis. Issue Volume 20:Issued 5(2019) (4th May 2019) - Hu, Jing; Liu, Pengfei; Wang, Dawei; Oeser, Markus; Canon Falla, Gustavo
ABSTRACT: Interface stripping is a common distress appeared in asphalt mixture due to the adhesive failure; it increases the cracks and decreases the strength and durability of pavement structure obviously. The aim of this paper is determining the influence of aggregate characteristics on interface stripping based on the microstructural finite element model. A high-resolution X-ray Computational Tomography device was used to scan the asphalt mixtures and provide their internal states; structures (Such as aggregate particles, asphalt mastic and air-voids) can be identified and reconstructed by Adaptive Digital Image Processing technique. Cohesive behaviour was selected to simulate the mechanical behaviour between aggregate particles and asphalt mastic, and then the evolution of interface damage can be evaluated. The investigation shows that the influence of aggregates on interface stripping is significant. Cracks are mainly appeared at the agg–mastic interface at high temperature; increasing the proportion of coarse aggregates cause more serious damage in agg–mastic interface; 3D fractal dimension is a quantitative indicator to evaluate the morphology and distribution of aggregates, and energy consumption presents a linear relationship with the 3D fractal dimension. This paper shows that microstructure can be used to reflect the damage and investigate the adhesive failure effectively.